Refractory airway type 2 inflammation in a large subgroup of asthmatic patients treated with inhaled corticosteroids - Peters, Michael C.; Kerr, Sheena; Dunican, Eleanor M.; Woodruff, Prescott G.; Fajt, Merritt L.; Levy, Bruce D.; Israel, Elliot; Phillips, Brenda R.; Mauger, David T.; Comhair, Suzy A.; Erzurum, Serpil C.; Johansson, Mats W.; et al. (Journal of allergy and clinical immunology, 2019)
Airway type 2 inflammation is usually corticosteroid sensitive, but the role of type 2 inflammation as a mechanism of asthma in patients receiving high-dose inhaled corticosteroids (ICSs) is uncertain. We sought to determine whether airway type 2 inflammation persists in patients treated with ICSs and to evaluate the clinical features of patients with steroid-resistant airway type 2 inflammation. We used quantitative PCR to generate a composite metric of type 2 cytokine gene expression (type 2 gene mean [T2GM]) in induced sputum cells from healthy control subjects, patients with severe asthma receiving ICSs (n = 174), and patients with nonsevere asthma receiving ICSs (n = 85). We explored relationships between asthma outcomes and T2GM values and the utility of noninvasive biomarkers of airway T2GM. Sputum cell T2GM values in asthmatic patients were significantly increased and remained high after treatment with intramuscular triamcinolone. We used the median T2GM value as a cutoff to classify steroid-treated type 2–low and steroid-resistant type 2–high (srT2-high) subgroups. Compared with patients with steroid-treated type 2–low asthma, those with srT2-high asthma were older and had more severe asthma. Blood eosinophil cell counts predicted srT2-high asthma when body mass index was less than 40 kg/m2 but not when it was 40 kg/m2 or greater, whereas blood IgE levels strongly predicted srT2-high asthma when age was less than 34 years but not when it was 34 years or greater. Despite ICS therapy, many asthmatic patients have persistent airway type 2 inflammation (srT2-high asthma), and these patients are older and have more severe disease. Body weight and age modify the performance of blood-based biomarkers of airway type 2 inflammation.